The Historical Narrative as an Object of Narratological Analysis - Žemgulis, Vytautas (Problemos, 2004)
Representatives of radical wing of philosophy of narrativistic history H. White and R. Ankersmit claim, that historical narrative is related to literary. Such proposition implicates that historical narration can be analysed by means of literature science. However so far, it seems that neither literature specialists nor philosophers of history have done this. In this article I will do my best to analyse the reasons why historical narrative has not been analysed on a literature aspect. Furthermore, after having explained the main notions of theory of literature narrative I will try to analyse an extract from History of Lithuania by E. Gudavičius in a narratological way and will present my own conclusions about the benefit of such analysis of historical narrative to philosophy of history.
Keywords: historical narrative; fictional narrative; narratology; narratological analysis